The Eye and Foot in Diabetes - Grigsby, Jeffery; Derbel, Fethi (IntechOpen, 2020)
In order to fully understand any disease, it is important to understand not only the potential end results of the condition, but how and why it develops to that point and the stages it passes through getting to that end. This book does not attempt to be a comprehensive treatise on how diabetic complications affect those who suffer from them or how they develop, but it does offer a collection of topics from distinguished scientists and clinicians covering the pathogenesis of damage, the clinical evaluation and treatment, and some surgical solutions to problems encountered in the diabetic eye and foot. It is not intended to be read cover to cover, although it could be, but rather offers specific information on topics of the diabetic eye and foot that should enlighten the reader. If you are a scientist, clinician, or surgeon, we hope you find the information presented here as useful as we did collecting it.